Flame-retardant pc / abs material and method for producing the same

CN116285287BActive Publication Date: 2026-10-30JIANGSU HAIJU NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310171154.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-27
Publication Date
2026-10-30
Estimated Expiration
2043-02-27

AI Technical Summary

Technical Problem

[0004]目前研究中使用较多的磷系阻燃剂是双酚A双(二苯基磷酸酯)和间苯二酚(二苯基磷酸酯),这两种阻燃剂常温下均为液态,在实际生产中需要专门的液体泵来将这两种液体阻燃剂加入到双螺杆挤出机中,整套设备成本较高且日常维护较为繁琐

Benefits of technology

[0042]1、本发明使用了一种新颖的阻燃体系,具体的是结合膨胀型阻燃剂(IFR)+协效阻燃剂+有机-无机杂化螺旋二氧化硅纤维,具体的阻燃机理为多方面的组合:1)气相阻燃机理,膨胀型阻燃剂(IFR)的分解释放出大量NH3、H2O等不燃气体降低氧气浓度,PO2等气相淬灭剂与聚合物自由基反应,有效抑制燃烧的进行。2)凝聚相阻燃机理,复合材料热解和APP分解时,磷酸和磷酸盐等酸性物质可以促进催化成炭,与协效阻燃剂(纳米硅酮粉)分解的硅氧烷反应,在材料表面可形成特殊的Si-O-P-C含硅无机陶瓷化致密残炭层,阻隔热氧交换,达到阻止燃烧的目的,另外,全氟丁基磺酸钾在高温下可以促进PC的降解,同时使PC树脂发生异构化现象,从而进一步交联和炭化。所以全氟丁基磺酸钾增加了PC的成炭速度,和磷酸酯阻燃剂相互促进,提高了材料的阻燃性能。3)有机-无机杂化螺旋二氧化硅纤维使高分子材料的分子链相互交叉缠绕,解决了熔融低落问题,大大减缓了燃烧速度,提高了极限氧指数,从而实现了阻燃的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004098611740000021
    Figure BDA0004098611740000021
  • Figure BDA0004098611740000031
    Figure BDA0004098611740000031
  • Figure BDA0004098611740000041
    Figure BDA0004098611740000041
Patent Text Reader

Abstract

The application discloses a kind of flame-retardant PC / ABS materials and preparation method thereof, belong to thermoplastic plastic material field.The application introduces synergistic flame retardant, organic-inorganic hybrid spiral silica fiber in intumescent flame-retardant system, and prepares a kind of halogen-free flame-retardant PC / ABS composite material, the flame-retardant PC / ABS composite material is not only excellent flame-retardant effect, but also smokeless, nontoxic, efficient, in addition, it is excellent in physical mechanics performance and apparent performance etc., with wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of thermoplastic materials, specifically relating to a flame-retardant PC / ABS material and its preparation method. Background Technology

[0002] Polycarbonate (PC) possesses advantages such as high heat resistance, high impact resistance, high gloss, good transparency, and excellent dimensional stability. However, it also has disadvantages such as susceptibility to stress cracking, poor processing flowability, poor solvent resistance, and notch sensitivity, which limit its application in the field of engineering plastics. PC exhibits good flame retardant properties, achieving UL94 V-2 rating, which is superior to other engineering materials.

[0003] Acrylonitrile-butadiene-styrene terpolymer (ABS) is a thermoplastic engineering plastic with a wide processing temperature range, good processing fluidity, and impact resistance. However, its mechanical properties and heat resistance are not ideal, limiting its applications. Blending PC and ABS to prepare PC / ABS alloys allows for complementary properties. On one hand, it improves the heat resistance and mechanical properties of ABS; on the other hand, it reduces the melt strength of PC, improving processing performance and reducing the stress sensitivity of the finished product. Therefore, PC / ABS alloys are widely used in automobiles, machinery, home appliances, communication tools, and office equipment. However, PC / ABS has a limiting oxygen index (LOI) of only 19.8%, classifying it as flammable and failing the vertical burning (UL-94) test. Flame retardants are typically added to improve the flame retardant properties of PC / ABS alloys. Halogenated flame retardants, such as phenoxytetrabromobisphenol A carbonate oligomers and brominated epoxy resins suitable for PC, have high flame retardant efficiency but produce large amounts of smoke and toxic gases during combustion. Following the enactment of the EU RoHS and WEEE directives, the use of halogenated flame-retardant PC / ABS has gradually decreased, replaced by halogen-free flame-retardant PC / ABS. The mainstream halogen-free flame retardants are phosphorus-based and silicone-based, with phosphorus-based flame retardants being more widely used in the market. For example, Gou Jia et al. found that polyphenoxyphosphate-2-10-hydro-9-oxa-phosphaphenanthrene hydroquinone can accelerate the charring of PC / ABS at high temperatures, reducing the polymer's contact with oxygen and thus achieving a flame-retardant effect. When added at 15%, it can achieve a UL94 V-0 rating. Li Ziqian et al. added 15% of the phosphorus-based flame retardant PK-3001 to PC / ABS, and the material achieved a UL94 V-2 flame retardant rating. Shao Jiali et al. selected triphenyl phosphate (TPP) as a flame retardant, adding 20 parts. Adding 2 parts of methyl acrylate-butadiene-styrene terpolymer (MBS) simultaneously improved the material's flame retardancy to UL94 V-0, but found that the addition of MBS worsened the flame retardant performance. Jiang Huimin et al. compounded TPP with thermoplastic phenolic resin to form an intumescent flame-retardant system for PC / ABS alloys. The best overall performance was observed when the mass ratio of the two flame retardants was 1:1 and the total addition amount was 11 parts. HSKwang et al. grafted TPP onto butadiene in the ABS molecular chain, increasing the compatibility between the flame retardant and the matrix. When the flame retardant addition amount was 8 parts, the material achieved UL94 V-0, and the Vicat softening temperature was higher than when only triphenyl phosphate was added. Li Xiaotang et al. found that resorcinol bis(2,6-dimethylphenyl phosphate) could replace antimony bromide flame retardant in PC / ABS alloys. Wei Fenfen et al. found that in the TPP flame-retardant PC / ABS system, MBS has a better compatibilizing effect on the system than styrene-maleic anhydride copolymer, and the material has higher impact strength when the MBS addition amount is 6%.

[0004] Currently, the most commonly used phosphorus-based flame retardants in research are bisphenol A (diphenyl phosphate) and resorcinol (diphenyl phosphate). Both of these flame retardants are liquid at room temperature, requiring specialized liquid pumps to add them to the twin-screw extruder in actual production. This equipment setup is costly and requires complex daily maintenance. Another commonly used phosphorus-based flame retardant is TPP. Although TPP is solid at room temperature, it has a low phosphorus content, resulting in low flame retardant efficiency. It requires large addition amounts, has a strong plasticizing effect, and significantly impacts the mechanical properties, especially the toughness, of PC / ABS alloys.

[0005] However, a single flame retardant cannot meet the requirements of high-efficiency flame retardancy. It is often necessary to combine multiple flame retardants for flame retardancy. Therefore, it is necessary to seek new flame retardant modification methods and prepare new high-efficiency flame retardants. This is the main development trend of flame-retardant PC / ABS materials in the future. Summary of the Invention

[0006] Objective of the Invention: To overcome the shortcomings of existing technologies, this invention provides a high-efficiency halogen-free flame-retardant PC / ABS material and its preparation method. This invention prepares a halogen-free flame-retardant PC / ABS composite material by introducing a synergistic flame retardant agent and organic-inorganic hybrid spiral silica fiber into an intumescent flame-retardant system. This flame-retardant PC / ABS composite material not only exhibits excellent flame-retardant performance but is also smokeless, non-toxic, and highly efficient. Furthermore, it demonstrates excellent physical and mechanical properties and appearance, showing broad application prospects.

[0007] Technical Solution: To achieve the above-mentioned objectives, the technical solution of this invention is as follows:

[0008] On one hand, the present invention provides a flame-retardant PC / ABS material, wherein the flame-retardant PC / ABS material comprises raw materials in the following weight ratio:

[0009]

[0010]

[0011] Specifically, the toughening agent is an acrylate-organosilicon copolymer.

[0012] More specifically, the content of organosilicon in the acrylate-organosilicon copolymer is 30-50%.

[0013] Specifically, the intumescent flame retardant is a compound of pentaerythritol (PER), ammonium polyphosphate (APP), and melamine.

[0014] More specifically, the mass ratio of pentaerythritol, ammonium polyphosphate, and melamine is 3:9:5.

[0015] More specifically, the content of ammonium orthophosphate in the ammonium polyphosphate is 10-25%.

[0016] Specifically, the synergistic flame retardant is a composition of silicone powder (GM), triphenyl phosphate (TPP), and potassium perfluorobutyl sulfonate.

[0017] More specifically, the mass ratio of the silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate is 2:3:3.

[0018] More specifically, the silicone powder contains ≥60% organosilicon.

[0019] Specifically, the organic-inorganic hybrid spiral silica fiber is prepared using 1,4-bis(triethoxysilyl)benzene (BTEB) as the silicon source.

[0020] More specifically, the preparation method of the organic-inorganic hybrid helical silica fiber includes the following steps: taking chiral anionic surfactant C 11 H 23 CO-L-Val-CO-NH-C 10 H 22 COO - Na + Place the mixture in a container, add deionized water and anhydrous ethanol as solvents, and under low temperature conditions with a shear force of Vox = 5, first add APTMS, then add 1,4-bis(triethoxysilyl)benzene (BTEB), stir until homogeneous, and after the reaction is complete, let it stand overnight, then heat it in an oil bath at 80℃ for 3-5 days. After the hydrothermal treatment is completed, remove the organic small molecule template with ethanol and concentrated hydrochloric acid, repeat the operation 3 times, and then dry to obtain organic-inorganic hybrid helical silica fibers.

[0021] In some embodiments, the preparation method of the organic-inorganic hybrid helical silica fiber of the present invention is as follows: 22g of chiral anionic surfactant C is weighed. 11 H 23 CO-L-Val-CO-NH-C 10 H 22 COO - Na +The solution was placed in a container and 2.2 L of deionized water and 1.8 L of anhydrous ethanol were added as solvents. At 0°C and a shear force of Vox = 5, 10 mL of APTMS was added, followed by 30 mL of 1,4-bis(triethoxysilyl)benzene (BTEB) at 5-second intervals. The mixture was stirred for 4 minutes. After the reaction was complete, the solution was left to stand overnight, then heated in an oil bath at 80°C for 4 days. After hydrothermal treatment, the organic small molecule template was removed using 4 L of ethanol and 1 L of concentrated hydrochloric acid. This process was repeated three times. The solution was then dried to obtain organic-inorganic hybrid helical silica fibers.

[0022] More specifically, the organic-inorganic hybrid helical silica fiber is a molecular chain cross-entanglement agent, wherein the fiber length is 0.1-5μm and the pitch is 400nm.

[0023] Specifically, the anti-aging additive is a hindered amine light stabilizer.

[0024] On the other hand, the present invention provides a method for preparing the above-mentioned flame-retardant PC / ABS material, the method comprising the following steps:

[0025] (1) Dry mix PC, ABS, toughening agent, intumescent flame retardant, synergistic flame retardant, organic-inorganic hybrid spiral silica fiber, and anti-aging additive in a high-speed mixer for 3-5 minutes;

[0026] (2) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion. The process is as follows: Zone 1 230-240℃, Zone 2 235-255℃, Zone 3 240-250℃, Zone 4 240-250℃, Zone 5 250-260℃, Zone 6 260-270℃, Zone 7 270-280℃, Zone 8 270-280℃, Zone 9 265-275℃, Zone 10 260-270℃; Residence time is 1-2 minutes, back pressure is 0.3MPa, and pressure is 12-18MPa.

[0027] Specifically, the flame-retardant PC / ABS material comprises the following raw materials in the indicated weight ratios:

[0028]

[0029] Specifically, the toughening agent is an acrylate-organosilicon copolymer.

[0030] More specifically, the content of organosilicon in the acrylate-organosilicon copolymer is 30-50%.

[0031] Specifically, the intumescent flame retardant is a compound of pentaerythritol (PER), ammonium polyphosphate (APP), and melamine.

[0032] More specifically, the mass ratio of pentaerythritol, ammonium polyphosphate, and melamine is 3:9:5.

[0033] More specifically, the content of ammonium orthophosphate in the ammonium polyphosphate is 10-25%.

[0034] Specifically, the synergistic flame retardant is a composition of silicone powder (GM), triphenyl phosphate (TPP), and potassium perfluorobutyl sulfonate.

[0035] More specifically, the mass ratio of the silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate is 2:3:3.

[0036] More specifically, the silicone powder contains ≥60% organosilicon.

[0037] Specifically, the organic-inorganic hybrid spiral silica fiber is prepared using 1,4-bis(triethoxysilyl)benzene (BTEB) as the silicon source.

[0038] More specifically, the preparation method of the organic-inorganic hybrid helical silica fiber includes the following steps: taking chiral anionic surfactant C 11 H 23 CO-L-Val-CO-NH-C 10 H 22 COO - Na + Place the mixture in a container, add deionized water and anhydrous ethanol as solvents, and under low temperature conditions with a shear force of Vox = 5, first add APTMS, then add 1,4-bis(triethoxysilyl)benzene (BTEB), stir until homogeneous, and after the reaction is complete, let it stand overnight, then heat it in an oil bath at 80℃ for 3-5 days. After the hydrothermal treatment is completed, remove the organic small molecule template with ethanol and concentrated hydrochloric acid, repeat the operation 3 times, and then dry to obtain organic-inorganic hybrid helical silica fibers.

[0039] More specifically, the organic-inorganic hybrid helical silica fiber is a molecular chain cross-entanglement agent, wherein the fiber length is 0.1-5μm and the pitch is 400nm.

[0040] Specifically, the anti-aging additive is a hindered amine light stabilizer.

[0041] Compared with the prior art, the positive and beneficial effects of the present invention are as follows:

[0042] 1. This invention utilizes a novel flame-retardant system, specifically combining an intumescent flame retardant (IFR) + a synergistic flame retardant + an organic-inorganic hybrid spiral silica fiber. The specific flame-retardant mechanism involves a combination of factors: 1) Gas-phase flame-retardant mechanism: The decomposition of the intumescent flame retardant (IFR) releases a large amount of non-combustible gases such as NH3 and H2O, reducing the oxygen concentration. Gas-phase quenchers such as PO2 react with polymer free radicals, effectively inhibiting combustion. 2) Condensed-phase flame-retardant mechanism: During the pyrolysis of the composite material and the decomposition of APP, acidic substances such as phosphoric acid and phosphates can promote catalytic char formation. These react with the siloxanes decomposed by the synergistic flame retardant (nano-silicone powder), forming a special Si-OPC silicon-containing inorganic ceramicized dense residual char layer on the material surface. This layer blocks heat and oxygen exchange, achieving the purpose of preventing combustion. In addition, potassium perfluorobutyl sulfonate can promote the degradation of PC at high temperatures, while simultaneously causing isomerization of the PC resin, thereby further cross-linking and carbonization. Therefore, potassium perfluorobutyl sulfonate increases the char formation rate of PC and promotes the interaction with phosphate ester flame retardants, thereby improving the flame retardant performance of the material. 3) Organic-inorganic hybrid spiral silica fibers cause the molecular chains of polymer materials to intertwine, solving the problem of melting and dripping, greatly slowing down the burning rate, and increasing the limiting oxygen index, thus achieving the flame retardant effect.

[0043] 2. This invention reduces the amount of intumescent flame retardant used by combining materials, but greatly improves the flame retardant efficiency. By introducing silicone powder (GM), triphenyl phosphate (TPP), and potassium perfluorobutyl sulfonate, and using acrylate-organosilicon copolymer toughening agent in combination, the compatibility between materials is greatly improved. While ensuring high flame retardancy, the mechanical properties are also greatly improved, and the appearance properties of the materials are also improved.

[0044] 3. The flame retardant used in this invention is an intumescent flame retardant. The additional synergistic flame retardants are silicone powder (GM), triphenyl phosphate (TPP), potassium perfluorobutyl sulfonate, and organic-inorganic hybrid spiral silica fiber. The decomposition products are substances such as NH3, CO2, and H2O. It is economical, smokeless, and non-toxic.

[0045] 4. The preparation process of the high-efficiency halogen-free flame-retardant PC / ABS material described in this invention is simple and low-cost.

[0046] 5. The halogen-free flame-retardant PC / ABS material obtained by this invention has a non-crosslinked structure and can be recycled and reused as ordinary PC / ABS material without causing secondary pollution. Detailed Implementation

[0047] The present invention will be further described in detail below with reference to specific embodiments. The following embodiments are not intended to limit the present invention, but only to illustrate the present invention. Unless otherwise specified, the experimental methods used in the following embodiments are generally performed under conventional conditions. Unless otherwise specified, the materials and reagents used in the following embodiments are commercially available.

[0048] Experimental materials

[0049] 1.PC.

[0050] 2.ABS.

[0051] 3. Toughening agent: acrylate-organosilicon copolymer, wherein the content of organosilicon in the acrylate-organosilicon copolymer is 30-50%.

[0052] 4. Intumescent flame retardant: The mass ratio of pentaerythritol, ammonium polyphosphate and melamine is 3:9:5, of which the content of ammonium orthophosphate in the ammonium polyphosphate is 10-25%.

[0053] 5. Synergistic flame retardant: The mass ratio of silicone powder, triphenyl phosphate and potassium perfluorobutyl sulfonate is 2:3:3, wherein the silicone powder contains ≥60% organosilicon.

[0054] 6. Organic-inorganic hybrid spiral silica fiber: The preparation method is as follows: Weigh 22g of chiral anionic surfactant C 11 H 23 CO-L-Val-CO-NH-C 10 H 22 COO - Na + The solution was placed in a container and 2.2 L of deionized water and 1.8 L of anhydrous ethanol were added as solvents. At 0°C and a shear force of Vox = 5, 10 mL of APTMS was added, followed by 30 mL of 1,4-bis(triethoxysilyl)benzene (BTEB) at 5-second intervals. The mixture was stirred for 4 minutes. After the reaction was complete, the solution was left to stand overnight, then heated in an oil bath at 80°C for 4 days. After hydrothermal treatment, the organic small molecule template was removed using 4 L of ethanol and 1 L of concentrated hydrochloric acid. This process was repeated three times. The solution was then dried to obtain organic-inorganic hybrid helical silica fibers.

[0055] 7. Anti-aging additives: hindered amine light stabilizers.

[0056] Example 1

[0057] The following components are mixed in a high-speed mixer for 3-5 minutes: 66% PC, 22% ABS, 3% toughening agent, 9% intumescent flame retardant, 8% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0058] Example 2

[0059] The following mixtures are prepared: 55% PC, 22% ABS, 4% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0060] Example 3

[0061] The following components are mixed in a high-speed mixer for 3-5 minutes: 42% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0062] Example 4

[0063] The following components are mixed in a high-speed mixer for 3-5 minutes: 35% PC, 41% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0064] Example 5

[0065] 40% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 8% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes, Back pressure: 0.3MPa, Pressure: 12-18MPa.

[0066] Example 6

[0067] The following components are mixed in a high-speed mixer for 3-5 minutes: 42% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0068] Example 7

[0069] The following components are mixed in a high-speed mixer for 3-5 minutes: 44% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 4% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0070] Example 8

[0071] The following components are mixed in a high-speed mixer for 3-5 minutes: 48% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0072] Example 9

[0073] 40% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 5% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes, Back pressure: 0.3MPa, Pressure: 12-18MPa.

[0074] Example 10

[0075] The following components are mixed in a high-speed mixer for 3-5 minutes: 42% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 3% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0076] Example 11

[0077] The following components are mixed in a high-speed mixer for 3-5 minutes: 43% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, 2% organic-inorganic hybrid spiral silica fiber, and 1% anti-aging additive. The mixture is then melt-extruded and granulated in a twin-screw extruder. The process parameters are: Zone 1: 230-240℃, Zone 2: 235-255℃, Zone 3: 240-250℃, Zone 4: 240-250℃, Zone 5: 250-260℃, Zone 6: 260-270℃, Zone 7: 270-280℃, Zone 8: 270-280℃, Zone 9: 265-275℃, Zone 10: 260-270℃; Residence time: 1-2 minutes; Back pressure: 0.3 MPa; Pressure: 12-18 MPa.

[0078] Example 12

[0079] 45% PC, 34% ABS, 5% toughening agent, 9% intumescent flame retardant, 6% synergistic flame retardant, and 1% anti-aging additive are dry-mixed in a high-speed mixer for 3-5 minutes. Then, the mixture is melt-extruded and granulated in a twin-screw extruder. The process is as follows: Zone 1 230-240℃, Zone 2 235-255℃, Zone 3 240-250℃, Zone 4 240-250℃, Zone 5 250-260℃, Zone 6 260-270℃, Zone 7 270-280℃, Zone 8 270-280℃, Zone 9 265-275℃, Zone 10 260-270℃; residence time is 1-2 minutes, back pressure is 0.3MPa, and pressure is 12-18MPa.

[0080] Experiment Example 1. Performance Evaluation

[0081] The granulated material prepared by the above method is dried in a forced-air oven at 60°C for 2-3 hours before being injection molded on an injection molding machine.

[0082] Tensile properties were tested according to ISO 527-2, with a specimen size of 150*10*4mm and a tensile speed of 50mm / min; flexural properties were tested according to ISO 178, with a specimen size of 80*10*4mm, a bending speed of 2mm / min, and a span of 64mm; simply supported beam impact strength was tested according to ISO 179, with a specimen size of 80*6*4mm and a notch depth of one-third of the specimen thickness; flame retardancy was tested according to UL94, with a specimen size of 127*12.7*1.6mm. The limiting oxygen index (LOI) was measured using a limiting oxygen indexer.

[0083] The formulations and performance test results of Examples 1-12 are shown in Table 1 below.

[0084] Table 1. Formulations and material properties of Examples 1-12

[0085]

[0086]

[0087] As can be seen from Examples 1-4, the PC / ABS system, which combines intumescent flame retardants, synergistic flame retardants, organic-inorganic hybrid spiral silica fibers, etc., has a high extreme oxygen index and good flame retardant effect, achieving a V0 rating.

[0088] A comparison of Examples 5-7 and Example 8 shows that the addition of the synergistic flame retardant (silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate complex) not only significantly improves the mechanical properties of the material but also increases the limiting oxygen index (LOI) and enhances the flame retardant effect. This is because the addition of silicone powder greatly improves the compatibility between the intumescent flame retardant and the composite material. Furthermore, during the pyrolysis of the composite material and the decomposition of APP, acidic substances such as phosphoric acid and phosphates can promote catalytic char formation. This char reacts with the siloxanes decomposed by the synergistic flame retardant (nano-silicone powder), forming a special Si-OPC silicon-containing inorganic ceramicized dense residual char layer on the material surface. This layer blocks heat and oxygen exchange, achieving efficient combustion prevention. Additionally, potassium perfluorobutyl sulfonate can promote the degradation of PC at high temperatures and simultaneously cause isomerization of the PC resin, further cross-linking and carbonizing it. Therefore, potassium perfluorobutyl sulfonate increases the char formation rate of PC and mutually promotes the flame retardant effect with the phosphate ester flame retardant, thus improving the flame retardant performance of the material.

[0089] A comparison of Examples 9-11 and Example 12 shows that the addition of organic-inorganic hybrid spiral silica fiber increases the limiting oxygen index (LOI) of the material and also improves its mechanical properties. This is because the organic-inorganic hybrid spiral silica fiber has good compatibility with PC / ABS. The organic-inorganic hybrid spiral silica fiber causes the molecular chains of the polymer material to intertwine, solving the problem of melting and dripping, greatly slowing down the combustion rate, increasing the limiting oxygen index, thereby achieving a flame-retardant effect and optimizing the material's performance.

[0090] In summary, the flame retardant system of this invention is based on an intumescent flame retardant system (pentaerythritol, ammonium polyphosphate, and melamine), combined with synergistic flame retardants (silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate), and introduces organic-inorganic hybrid spiral silica fibers. This improves the flame retardant effect of the material from multiple aspects, including the gas phase, condensed phase, and the material itself. Combined with the improved compatibility of the material, the method is not only novel and flexible in design, but also highly efficient in flame retardancy, smokeless, non-toxic, pollution-free, and with excellent mechanical properties.

[0091] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A flame-retardant PC / ABS material, characterized in that: The flame-retardant PC / ABS material comprises the following raw materials in the indicated weight ratios: The intumescent flame retardant is a compound of pentaerythritol, ammonium polyphosphate, and melamine; The synergistic flame retardant is a composition of silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate; The preparation method of the organic-inorganic hybrid helical silica fiber includes the following steps: taking chiral anionic surfactant C 11 H 23 CO-L-Val-CO-NH-C 10 H 22 COO - Na + Place the mixture in a container, add deionized water and anhydrous ethanol as solvents, and under low temperature conditions with a shear force of Vox=5, first add APTMS, then add 1,4-bis(triethoxysilyl)benzene, stir until homogeneous, and after the reaction is complete, let it stand overnight, then heat it in an oil bath at 80℃ for 3-5 days. After the hydrothermal treatment is completed, remove the organic small molecule template with ethanol and concentrated hydrochloric acid, repeat the operation 3 times, and then dry to obtain organic-inorganic hybrid helical silica fibers.

2. The flame-retardant PC / ABS material according to claim 1, characterized in that: The toughening agent is an acrylate-organosilicon copolymer, wherein the content of organosilicon in the acrylate-organosilicon copolymer is 30-50%.

3. The flame-retardant PC / ABS material according to claim 2, characterized in that: The mass ratio of pentaerythritol, ammonium polyphosphate, and melamine is 3:9:5; the content of ammonium orthophosphate in the ammonium polyphosphate is 10-25%.

4. The flame-retardant PC / ABS material according to claim 3, characterized in that: The mass ratio of the silicone powder, triphenyl phosphate, and potassium perfluorobutyl sulfonate is 2:3:3; the silicone powder contains ≥60% organosilicon.

5. The flame-retardant PC / ABS material according to claim 4, characterized in that: The anti-aging additive is a hindered amine light stabilizer.

6. A method for preparing the flame-retardant PC / ABS material according to any one of claims 1-5, characterized in that: The method includes the following steps: (1) Dry mix PC, ABS, toughening agent, intumescent flame retardant, synergistic flame retardant, organic-inorganic hybrid spiral silica fiber, and anti-aging additive in a high-speed mixer for 3-5 minutes; (2) The mixed raw materials are placed in a twin-screw extruder and granulated by melt extrusion. The process is as follows: Zone 1 230-240℃, Zone 2 235-255℃, Zone 3 240-250℃, Zone 4 240-250℃, Zone 5 250-260℃, Zone 6 260-270℃, Zone 7 270-280℃, Zone 8 270-280℃, Zone 9 265-275℃, Zone 10 260-270℃; Residence time is 1-2 minutes, back pressure is 0.3MPa, and pressure is 12-18MPa.

Citation Information

Patent Citations

  • High performance flame retardant material

    CN104371253A

  • PC / ABS composite material as well as preparation method and application thereof

    CN112625420A